Optical properties of semiconductor “anisotropic” quantum dot - Lukiyanets, B.A.; Matulka, D.V. (Physics and Chemistry of Solid State, 2021)
The optical properties of an “anisotropic” semiconductor nanodot – a nanoscale object in the form of a rectangular parallelepiped - with sides a ≠ b ≠ c are considered. Such dimensions are closely related to the values of the effective masses of the electron. The analysis of the spectral dependence of the absorption coefficient a(w) under different degrees of "anisotropy" and under different polarizations of the electromagnetic wave is carried out. The cases of the most intense optical transitions, i.e. between electronic states separated by the Fermi level, are analyzed. The obtained results indicate that 1) a(w) is of line structure, and 2) the positions of the peaks of a(w) in identical optical transitions in the isotropic nanodot and in the “anisotropic” ones coincide qualitatively. However, different masses in the “anisotropic” nanodot lead to a shift to the left or right of the peaks relative to identical peaks in the isotropic nanodot with simultaneous splitting of its degenerate peaks. Such shifts and their magnitudes are determined both by the degree of anisotropy (i.e. by the ratio between the effective masses), and by the polarization of light. It is pointed out that modern achievements in the creation of ordered semiconductor materials with nanoobjects of different shapes and sizes in nanostructures allows us to consider polarized electromagnetic wave as an effective factor in achieving the desired physical characteristics.